Ga-PSMA-11 PET/CT in primary staging of prostate carcinoma: preliminary results on differences between black and white South-Africans. - Sathekge, Mike; Lengana, Thabo; Maes, Alex; Vorster, Mariza; Zeevaart, JanRijn; Lawal, Ismaheel; Ebenhan, Thomas; Van de Wiele, Christophe (European Journal of Nuclear Medicine & Molecular Imaging, 2018)
Purpose: The incidence of prostate cancer is 60% higher and the mortality rate is two- to three-times greater in black versus white men. We report on differences in Ga-PSMA-11 PET/CT imaging findings in 77 black South-African (BSAs) and 18 white South-African (WSAs) treatment-naïve primary prostate carcinoma (PPC) patients. Methods: Ga-PSMA-11 PET/CT imaging findings were compared to histological, biochemical and morphological imaging data. Patients were grouped into three Gleason grade groups (GG), GG 1 (scores 3 + 3 and 3 + 4), GG2 (scores 4 + 3 and 4 + 4) and GG3 (scores 9 and 10), and the PSA difference among the groups was determined. Inter-racial difference in SUVmax of the primary tumor as well as its correlation with serum PSA were also determined. Results: Ninety-three out of 95 PPC where readily identified on Ga-PSMA-11 PET/CT imaging. Median PPC SUVmax and serum PSA values proved significantly higher ( p = 0.033 and p = 0.003) in GG3 patients (median 16.4 and 180 ng/ml) when compared to GG1 patients (median 9.6 and 25.1 ng/ml) or GG2 patients (median 8.8 and 46.2 ng/ml). SUVmax significantly correlated with serum PSA-values ( r = 0.377 ( p = 0.0001)). Age, frequency of lymph node involvement and distant metastases, and GGs ( p ≥ 0.153) were similar in BSAs and WSAs, both median serum PSA-values as well as SUVmax values proved significantly higher in BSAs when compared to WSAs, respectively, 81.6 ng/ml versus 14.5 ng/ml ( p = 0.0001) and 11.9 versus 4.38 ( p = 0.004). Moreover, Gleason-score normalized median SUVmax values proved 2.5 times higher in BSAs when compared to WSAs ( p = 0.005). Conclusion: SUVmax values proved significantly related to GG and to be significantly higher in BSAs when compared to WSAs. Also, SUVmax significantly correlated with serum PSA values, which was significantly higher in BSAs when compared with WSAs.